Human diseases caused by homozygous PTH1R mutations - Portales-Castillo, Ignacio; Höppner, Jakob; Jüppner, Harald; Gardella, Thomas J. (Frontiers in Endocrinology, 2025)
The parathyroid hormone receptor type 1 (PTH1R) is a G protein-coupled receptor that mediates the actions of parathyroid hormone (PTH) in the regulation of blood calcium levels, as well as PTH-related protein (PTHrP) in the regulation of skeletal development. Severe loss-of-function homozygous mutations in PTH1R are incompatible with life as in Blomstrand’s lethal chondrodysplasia, characterized by accelerated growth plate ossification. More recently, homozygous mutations located in the transmembrane helices, extracellular domains and C-tail of the PTH1R were identified in patients with milder conditions characterized by variable degrees of skeletal and mineral abnormalities. These include delayed ossification in Eiken syndrome, hypocalcemia in a pseudohypoparathyroidism-like disorder, and non-syndromic primary failure of tooth eruption; which is usually caused by heterozygous PTH1R mutations. Recent detailed pharmacologic characterization of these PTH1R mutants has revealed new insights into how even subtle perturbations in PTH1R function can result in disease.